2008
DOI: 10.20452/pamw.458
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of plasma levels and diagnostic values of macrophage‑colony stimulating factor in patients with breast cancer and benign tumors

Abstract: INTRODUCTION Macrophage-colony stimulating factor (M-CSF) is one of the glycoproteins called hematopoetic growth factors. The direct production of this cytokine has been reported in tumor cell lines in vitro and in solid tumors in vivo. OBJECTIVES In the present study, the levels of M-CSF in patients with breast cancer and in those with a benign breast tumor were evaluated. Moreover, diagnostic values were determined through assesing diagnostic sensitivity and specificity as well as predictive value of positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…28 Secretion of M-CSF from BC cells is accompanied by the expression of its own R (CD115, in w50% of all tumors and 90% metastatic tumors), suggesting that this cytokine plays a role in the invasive process of BC cells. 29 Our observations related to CCL-2/CCR-2 are in accordance with those made by other authors that showed this chemokine interaction as a promoter of BC cell survival and motility. 30,31 On the other hand, we found that the expression of OPG, TRAIL, TRAIL-R1, TRAIL-R2, TRAIL-R3, TRAIL-R4, RANKL, RANK, CXCR-4, IL-6, IL-6R, and CCL-2 was significantly higher in spindle-shaped SC from patients with BC compared with the expression in non-neoplastic tissues.…”
Section: Vivian Labovsky Et Alsupporting
confidence: 93%
“…28 Secretion of M-CSF from BC cells is accompanied by the expression of its own R (CD115, in w50% of all tumors and 90% metastatic tumors), suggesting that this cytokine plays a role in the invasive process of BC cells. 29 Our observations related to CCL-2/CCR-2 are in accordance with those made by other authors that showed this chemokine interaction as a promoter of BC cell survival and motility. 30,31 On the other hand, we found that the expression of OPG, TRAIL, TRAIL-R1, TRAIL-R2, TRAIL-R3, TRAIL-R4, RANKL, RANK, CXCR-4, IL-6, IL-6R, and CCL-2 was significantly higher in spindle-shaped SC from patients with BC compared with the expression in non-neoplastic tissues.…”
Section: Vivian Labovsky Et Alsupporting
confidence: 93%